Diagnostic and Management Problems of a Patient with Severe Life-Threatening Acute Hypocalcemia: A Case Report - Arvin Wiranata Lianto; Birgita Maria Ratu Rosari Bas; Robert Dwitama Adiwinoto; Libriansyah Libriansyah (Biomolecular and Health Science Journal, 2022)
Hypocalcemia is a common electrolyte disorder. Acute hypocalcemia is a life-threatening condition that needs prompt evaluation and management. We present a case of a 54-year-old woman presented to emergency room with muscle spasm and involuntary movement. Upon physical examination, the patient was disoriented and the Trousseau’s sign was bilaterally positive when the cuff was inflated. Blood test revealed severe hypocalcemia with albumin-corrected serum total calcium levels 1.77 mg/dL. Following extensive diagnostic workups, there were no alternative explanations other than vitamin D deficiency. Despite aggressive intravenous (IV) calcium correction and high-dose vitamin D supplementation the calcium levels gradually decreased and neurological symptoms relapsed. The use of phenytoin to treat neurological symptoms decreased calcium levels further. The patient was eventually discharged with oral calcium and calcitriol supplementation with minimal symptoms. This case highlights the importance of thorough diagnostic workups and judicious use of anticonvulsant drugs in hypocalcemia for optimal treatment outcome.